2008
DOI: 10.1038/jp.2008.101
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative cardiorespiratory instability following ligation of the preterm ductus arteriosus is related to early need for intervention

Abstract: Objective: To investigate the effect of postnatal age at patent ductus arteriosus (PDA) ligation on postoperative need for cardiotropic support.Study Design: A significant proportion of premature infants with a hemodynamically significant ductus arteriosus (HSDA) require surgical intervention. The relationship of postnatal maturation to postoperative cardiorespiratory stability is poorly understood. All preterm neonates who underwent PDA ligation between October 2002 and September 2004 were identified and divi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
107
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(112 citation statements)
references
References 28 publications
2
107
1
2
Order By: Relevance
“…Left ventricular failure could lead to pulmonary edema and result in difficulty with oxygenation. 4,13 A study in the preterm baboon showed ligated animals had more severe left ventricular dysfunction, required more cardiovascular support and higher mean airway pressures at 24 h of age compared with animals with persistent PDA that is consistent with what we often see in this population. 14 This acute decompensation experienced by infants post ligation is important because it may place them at higher likelihood for poor long-term outcomes.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Left ventricular failure could lead to pulmonary edema and result in difficulty with oxygenation. 4,13 A study in the preterm baboon showed ligated animals had more severe left ventricular dysfunction, required more cardiovascular support and higher mean airway pressures at 24 h of age compared with animals with persistent PDA that is consistent with what we often see in this population. 14 This acute decompensation experienced by infants post ligation is important because it may place them at higher likelihood for poor long-term outcomes.…”
Section: Discussionmentioning
confidence: 61%
“…3 Prostaglandin inhibitors, such as indomethacin or ibuprofen, are used to close the PDA, but if pharmacological closure is contraindicated or unsuccessful, surgical ligation is usually performed in most neonatal intensive care units (NICU) according to present clinical practice. 4 Surgery is well tolerated in most infants, but B30% develop severe systemic hypotension and respiratory decline requiring maximum levels of cardiopulmonary support in the postoperative period. 5 It has been suggested that this postoperative cardiorespiratory instability is the reason why the infants that have PDA ligations are at higher risk for bronchopulmonary dysplasia, severe retinopathy of prematurity and neurosensory impairment.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence on the risks of drug therapy or surgical PDA ligation26, 27 has led to growing interest in the use of percutaneous closure in premature infants 10, 15, 16, 28, 29, 30. The main finding of our 10‐year study is that, among a large cohort of infants born very premature and referred for percutaneous closure at weights <4 kg, the majority are successfully closed in the catheterization suite with evidence of improved pulmonary status following closure, but risk of arterial injury in these infants is noteworthy.…”
Section: Discussionmentioning
confidence: 99%
“…In about 30% of preterm infants undergoing PDA ligation, there is some degree of cardiovascular compromise as evidenced by the need for initiation or escalation of vasopressorinotrope or inotrope treatment. [52][53][54] The reason for this deterioration is not known. In one study, lower gestational age, and higher respiratory support and, interestingly, exposure to antenatal steroids were associated with post-ligation hypotension.…”
Section: Surgical Closurementioning
confidence: 99%